Synthesis and Spectral Characterization of Ni(II) Complex of Hexahydrocyclotriphosphazene - Jain, Niklank; Jadon, S.P.S. (Asian Journal of Chemistry, 2010)
The Ni(II) complex of hexahydrocyclotriphosphazene [(NPH2)3]2 has been synthesized and investigated spectrometrically. Quantitative analysis and mass spectrum of the product assigned its molecular formula [(NPH2)3]2×NiSO4×6H2O. Its IR, UV and 1H NMR spectra have confirmed quadridentate N-coordinated complex formation.